Contribution of Chalena Vásquez to Peruvian music history’s teaching for school students - Caro Palomino, Francisco Alonso (2023)
The present research with qualitative approach, aims to analyze the contribution of musicologist Chalena Vasquez Rodriguez to Peruvian Music History’s teaching for school students, from the perspective of cultural artistic appreciation, the cultural identity approach and the rights approach. For the study, the documentary analysis technique and the documentary analysis sheet instrument were used. The booklet History of music in Peru prepared by Chalena Vásquez for the Ministry of Education was reviewed. Contributions were found in the dimensions of cultural rights, ethnomusicology, interculturality and music education research.